Complications of caesarean section. (October 2016) - Field, Alexander; Haloob, Rahim
Abstract : Key content: The incidence and presentation of complications of caesarean section. The surgical management of intrapartum and postpartum haemorrhage. Risk factors for, and prevention and treatment of postpartum sepsis. Presentation, investigation and repair of bladder injuries when recognised intraoperatively and following delayed presentation. Risk factors for, and recognition and management of suspected ureteric injury intraoperatively and postoperatively. Bowel complications including intraoperative bowel injury and management, postoperative ileus and Ogilvie syndrome. Particular risks and complications associated with caesarean section at full dilatation. Caesarean section in the developing world. Learning objectives: To be aware of the most common and serious complications of caesarean section. To be able to describe recognition and initial surgical management of suspected bladder, ureteric and bowel injuries. To be familiar with delayed presentations of visceral injuries and have a systematic approach to investigation of suspected injury. To understand the impact of caesarean section complications in resource‐poor countries. Ethical issues: Appropriate, accurate preoperative counselling regarding risks and consent. Awareness of personal competency in managing specific complications.